How a sensitive analysis on the coupling geology and borehole heat exchanger characteristics can improve the efficiency and production of shallow geothermal plants - Jessica Maria Chicco; Giuseppe Mandrone (Heliyon, 2022)
Knowledge of the thermal behaviour around and throughout borehole heat exchangers (BHEs) is essential for designing a low enthalpy geothermal plant. In particular, the type of grout used in sealing the space between BHE walls and the pipes is fundamental for optimizing the heat transfer and minimizing the thermal resistance, thereby promoting the reduction of total drilling lengths and installation costs. A comparison between grouts with different thermal conductivities coupled with common hydrogeological contexts, was modelled for a typical one-year heating for continental climates. These data have been used for a sensitivity analysis taking into account different flow rates through pipes. The results highlight that in groundwater transient conditions, porous lithologies allow for greater heat power extractions to be obtained with an increasing grout thermal conductivity than limestone or clayey silt deposits do. Moreover, increasing the inlet flow rates through the pipe greatly improves the final heat power extraction. As a result, when the underground allows for high extraction rates, the use of high performing grouts is warmly suggested ensuring greater productions.